2016
DOI: 10.4090/juee.2016.v10n1.106112
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional computational simulation flow of exhaust gases passing inside an electrostatic precipitator

Abstract: Abstract:In the present study the two-dimensional computational simulation flow of hot exhaust gases which are passed inside an electrostatic precipitator will be carried out. Initially, the theoretical background and necessary equations from fluid mechanics will be described. These equations will be used by software for flow simulation. Furthermore, are presented the design of precipitator through which the exhaust gases are passed. In the next step follows the declaration of various parameters of simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Again, a 2D CFD model was used in their investigations. Similar investigations in terms of velocity distribution in ESP were conducted by Kouropoulos [16]. Celik et al [17] in their own numerical investigations have found that porosity of the plate is the most effective design parameter in terms of pressure drop across the plate, while the least effective is the hole pattern.…”
Section: Previous Studies Of Modelling Of Flow Through Perforated Platesmentioning
confidence: 57%
“…Again, a 2D CFD model was used in their investigations. Similar investigations in terms of velocity distribution in ESP were conducted by Kouropoulos [16]. Celik et al [17] in their own numerical investigations have found that porosity of the plate is the most effective design parameter in terms of pressure drop across the plate, while the least effective is the hole pattern.…”
Section: Previous Studies Of Modelling Of Flow Through Perforated Platesmentioning
confidence: 57%